Association of positively selected eIF3a polymorphisms with toxicity of platinum-based chemotherapy in NSCLC patients - YIN Ji-ye; MENG Xiang-guang; QIAN Chen-yue; LI Xiang-ping; CHEN Juan; ZHENG Yi; LIU Rong; ZHOU Hong-hao; LIU Zhao-qian (Acta Pharmacologica Sinica; Vol 36, No 3 (March 2015): Acta Pharmacologica Sinica, 2017)
Aim: Eukaryotic translation initiation factor 3 subunit A (eIF3a) plays critical roles in regulating the initiation of protein translation, and eIF3a is highly expressed in lung cancer. In this study, we investigated the association of the positively selected SNPs of eIF3a with the response to and toxicity of platinum-based chemotherapy in Chinese patients with non-small cell lung cancer (NSCLC). Methods: SNP data for eIF3a locus were downloaded from HapMap database. For each SNP, haplotype, LD profile and population differentiation were analyzed. The long-range haplotype (LRH) test was employed to identify positively selected SNPs of eIF3a. A total of 325 NSCLC patients were enrolled and genotyped for these SNPs. Results: Five positively selected (rs1409314, rs4752219, rs4752220, rs7091672 and rs10510050) and 5 non-positively selected SNPs (rs10886342, rs11198804, rs2275112, rs10787899 and rs4752269) were identified in the LRH test. However, none of them was correlated with the platinum-based chemotherapy response. In contrast, 4 of the positively selected SNPs (rs1409314, rs4752219, rs4752220 and rs7091672) were significantly correlated with the toxicities tested (neutropenia, anemia, thrombocytopenia, emesis and hepatotoxicity). In addition, rs10510050 was significantly correlated with thrombocytopenia, emesis and hepatotoxicity. None of the 5 non-positively selected SNPs was correlated with the 5 toxicities. Conclusion: The positively selected SNPs of eIF3a are significantly correlated with platinum-based chemotherapy toxicities in Chinese NSCLC patients.